Identifying Risk Factors for Failure of a Modified Broström's Procedure. Issue 3 (14th September 2018) - Tadley, Madeline; Tan, Timothy; Shakked, Rachel; Daniel, Joseph; Raikin, Steven; Pedowitz, David
Category: Ankle Introduction/Purpose: The modified Broström's procedure has been widely accepted as the operative treatment of choice for treating lateral ankle instability in patients that have failed nonoperative management. However, the predisposing risk factors for failure of operative treatment, which has important implications for patient selection, is unknown. The purpose of this study is to thus identify independent risk factors for failure of an index Broström's procedure. Methods: A retrospective single institutional study of 123 modified Broström's procedures, average age 40 years, was performed with a minimum of 2 year follow-up. An electronic query based on Current Procedural Terminology codes was initially performed followed by a manual review of the operative report. Patients with any concurrent osteotomy, arthrodesis, or arthroplasty procedures were excluded. Foot and Ankle Ability Measure (FAAM) and Short Form Survey 12 (SF-12) were obtained both preoperatively and postoperatively. Cormorbidities and relevant demographic information were manually obtained. Treatment success was defined as a postoperative FAAM Sport score increase by greater than 9 points, an established minimal clinical difference established in the literature. A linear regression controlling demographic factors and baseline scores was utilized to predict scores at last follow-up. Results: At last follow-up, 31.4% did not demonstrate a self reported clinical improvement in the FAAM Sport scores with 2% (3/123) of the entire cohort requiring reoperation. A higher preoperative physical SF-12 score was associated with a reduction in the postoperative physical SF-12 score (p=0.035) while higher body mass index (p=0.010) was associated lower mental component SF-12 scores at follow-up. Interestingly, higher age is associated with higher 2-year PCS score. Furthermore, the occurrence of a complication was associated with lower ADL (p<0.001), Sport (p=0.002), and total FAAM (p=0.002) scores and higher pain (p=0.017) at 2-years. Conclusion: A significant amount of patients did not demonstrate a clinical improvement in functional outcomes although the overall reoperation rate was low. Surgeons should be aware that approximately one third of patients may not have achieved their desired clinical outcome and that BMI and preoperative function is associated with worse outcomes.